The cyberbullying in context university of Brazil and Portugal: victimization, emotions associates and coping strategies - Souza, Sidclay Bezerra de (2016)
The present article searched to describe how the university students of Portugal and Brazil they experienced the role of be victims in cyberbullying considering some sociodemographic variables as well as depending on the context in relation to the conduct of victimization, the emotions and the strategies used by victims of Brazil and Portugal students. Seeking to meet the objectives of the investigation, 1340 students (Brazil: n = 592; Portugal: n = 748) responded to the Cyberbullying Inventory for College Students (CICS). The analyzes allowed to verify that a percentage of 44.6% of participants from Brazil and 43.0% of participants from Portugal were victims of cyberbullying at some point in life and some differences were found with regard to the conduct of victimization, the emotions of victims and the coping strategies used by victims of each country. The results are discussed, some limitations are considered and are some implications that suggest the importance of systemic development of prevention and intervention programs in university contexts.